Comparison of mortality and cardiovascular complications due to COVID-19, RSV, and influenza in hospitalized children and young adults - Sagya Khanal; Bishes Khanal; Fu-Sheng Chou; Anita J. Moon-Grady; Laxmi V. Ghimire (BMC Cardiovascular Disorders)
Abstract Background Respiratory viruses are linked to cardiovascular complications. We aim to compare cardiovascular complications due to COVID-19, influenza and RSV. Methods We analyzed cross-sectional data from hospitalized children and young adults (≤ 20 years) from 2020 and 2021 using National Inpatient Sample (NIS). We included individuals hospitalized for COVID-19, RSV, and influenza, and weighted data were used to compare cardiovascular complications. Results Of 212,655 respiratory virus admissions, 85,055 were from COVID-19, 103,185 were from RSV, and 24,415 were from influenza. Myocarditis was higher in COVID-19 [0.9%, n = 740] as compared to influenza [0.2%, n = 55] and RSV [0.1%, n = 65]. In the adjusted logistic regression, the odds of myocarditis was 61% lower in influenza [aOR = 0.39 (0.20–0.76), P = 0.006], and 85% lower in RSV [aOR = 0.15 (0.07–0.34) P < 0.001] as compared to COVID-19. Bradyarrhythmias/heart block was higher in COVID-19 [0.8%, n = 690] versus influenza [0.5%, n = 110] and RSV [0.2%, n = 205]. After adjusting for confounders for bradyarrhythmias/heart block, compared to COVID-19, the odds were 49% lower in RSV [aOR = 0.51 (0.33–0.80), P = 0.004] but no statistically significant difference in influenza [aOR = 0.79 (0.48–1.31), P = 0.374] was seen. Tachyarrhythmias, sudden cardiac arrest, and in-hospital mortality showed no differences after adjusting for covariates. Conclusion Individuals with COVID-19 infection are more likely to develop cardiovascular complications compared to influenza and RSV, highlighting the need for higher index of suspicion and prompt treatment, as well as steps to limit infection and transmission of this virus in children.